THE INFLUENCE OF PARENTAL CLASS ON EARLY CHILDHOOD CLEAN AND HEALTHY LIVING BEHAVIOR - Ani Mulyani; Rivo Panji Yudha; Nor Ilman Syaputra; Lina Marlina; Uswatun; Nihayaturaochmah; Yulyati Mulyanto; Adolfiron Luji (Universitas Panca Sakti Bekasi, 2024)
This study aims to determine the effect of the implementation of parent classes on clean and healthy living behavior of children aged 5-6 years in SPS Yaman Nurjati, Kertasmaya District, Indramayu Regency. This study used Pre-Experimental Designs with One Group Pretest-Posttest Design. One Group Pretest-Posttest Design. Researchers also conducted validity and reliability tests. Based on statistical data analysis paired sample t-test. The calculated t value is 10.793 with a significance value (2-tailed) of 0.001. Based on these data that the value of 0.001 <0.05, thus it can be concluded that the implementation of parental classes affects the clean and healthy behavior of early childhood.